The Fragile and Inappropriate Political, Social, and Economic Situation in Pakistan - Khpalwak Zazai, Abuzar; Najeebrahman Rahmani (Universitas Muhammadiyah Malang, 2024)
Abstract Due to the increasing political, security, social, and economic challenges in Pakistan, it is necessary for everyone to have a better and more accurate understanding of it to have a clear picture of the current situation in Pakistan. The aim of highlighting the above-mentioned topics is to provide a comprehensive roadmap for identifying, analyzing, and solving issues and problems that have hindered the development and progress of the country, especially when officials are not saying much about it. This research utilizes both quantitative and qualitative methods to extract findings. Based on the analysis and evaluation of the political, security, social, and economic situation of Pakistan, it can be said that country is in a precarious situation and its management is beyond the capacity of its rulers and politicians. If this situation continues, it is possible that the country's situation will become more volatile in the near future, and in that case, the possibility of Pakistan's disintegration in the coming years is conceivable. Abstrak Peningkatan tantangan politik, keamanan, sosial, dan ekonomi di Pakistan membuat setiap orang perlu memiliki pemahaman yang lebih baik dan lebih akurat untuk memiliki gambaran yang jelas tentang situasi saat ini di Pakistan. Tujuan penulisan ini adalah menyoroti topik-topik yang disebutkan di atas adalah untuk memberikan peta jalan yang komprehensif untuk mengidentifikasi, menganalisis, dan memecahkan masalah yang telah menghambat pembangunan dan kemajuan negara, terutama ketika para pejabat tidak banyak bicara tentang hal itu. Penelitian ini menggunakan metode kuantitatif dan kualitatif untuk mengekstrak temuan. Berdasarkan analisis dan evaluasi situasi politik, keamanan, sosial, dan ekonomi Pakistan, dapat dikatakan bahwa negara berada dalam situasi genting dan pengelolaannya berada di luar kapasitas penguasa dan politisinya. Jika situasi ini terus berlanjut, ada kemungkinan situasi negara akan menjadi lebih fluktuatif dalam waktu dekat, dan dalam hal ini, kemungkinan disintegrasi Pakistan di tahun-tahun mendatang dapat dibayangkan.